Possible relationship between prescription medications and urinary dysfunction in elderly home health care patients - Yamada, Shizuo; Mizukami, Katsuyoshi; Watanabe, Yoriko; Higashino, Sadanori; Miyazaki, Sayaka (Nihon Rōnen Igakkai zasshi, 2019)
Aim: Although urinary incontinence (UI) in the elderly appears to be related to polypharmacy, it is unclear whether multiple medications elevate UI quantitatively or qualitatively. There have been few studies on the association of polypharmacy with each type of UI. The present survey aimed to clarify these issues.Method: The subjects were elderly home health care patients ≥65 years of age taking ≥5 prescription medications and not being treated with anti-cancer agent. The visiting nurses filled out a questionnaire based on their nursing and medication records. Types of UI were evaluated according to a UI checklist.Results: A total of 167 subjects (97 women, 70 men, mean age of 83.8 years) were eligible for the data analysis. Subjects talking 5-9 prescription medications accounted for 59.3%, while those talking≥10 counted for 40.7%. Men talking ≥10 medications showed a slight but non-significant increased risk of UI. In women, α-adrenergic antagonists and benzodiazepines significantly increased the risk of stress UI and urge UI, respectively. Furthermore, α-adrenergic antagonists reduced the risk of functional UI, whereas acetylcholinesterase inhibitors elevated it. α-adrenergic antagonists in combination with benzodiazepines also significantly increased the risk of stress UI and urge UI, while α-adrenergic antagonists with acetylcholinesterase inhibitors increased the risk of stress UI. In men, there were no prescription medications that were particularly related to UI.Conclusions: The present results suggest that there are gender differences in prescription medications-induced UI. It is likely that the causing medications are different depending on the type of UI, and the combination of them significantly increase the risk of UI.